United Kingdom Myeloma Forum (UKMF) position statement on the use of bendamustine in myeloma. (25th April 2013) - Pratt, G.; Bowcock, S.; Lai, M.; Bell, S.; Bird, J.; D'Sa, S.; Cavenagh, J.; Cook, G.; Morgan, G.; Owen, R.; Snowden, J.A.; Yong, K.; et al.
Summary Bendamustine is a unique bifunctional alkylating agent with promising activity in myeloma. Despite the increasing number of studies demonstrating its efficacy in both the upfront and relapse settings, including patients with renal insufficiency, the optimal use of bendamustine, in terms of dosage, schedule and combination with other agents, has yet to be defined. It is currently licensed for use as frontline treatment with prednisolone for patients with myeloma who are unsuitable for transplantation and who are contraindicated for thalidomide and bortezomib. Studies in relapsed/refractory patients are currently ongoing with other combinations. Given the increasing data to date, the UK Myeloma Forum believes that bendamustine with steroids alone or in combination with a novel agent could be considered for patients with multiply relapsed myeloma. This document provides guidance for the use of bendamustine for patients with myeloma until the results of definitive studies are available.